Physiochemical and Antibacterial Studies of Two Tetradentate Ligands Type (N2O2) and Their Complexes withCoII, NiII and ZnII Ions - Hasan A. Hasan; khaled salman (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2018)
Two tetradentate ligands type (N2O2) and their complexes with CoII, NiII and ZnII ions were synthesized via two steps; in the first, the precursors W1 and W2 were synthesized from the reaction of  2,6-diamine pyridine or 2,4-diamine tolylene with 2,5-hexanedione respectively in a 2:1 mole ratio. In the second step the ligands [H2L1] and [H2L2] were prepared from the reaction of the two precursorâ€™s with 2-hydroxy-1-naphthaldehyde in 1:2 mole ratio. Metal complexes were synthesized by the reaction of the ligands with equivalent amounts of the metal chloride. The prepared compounds were characterized with the physiochemical and spectral techniques which confirmed tetrahedral structure around the metal ions. The antibacterial activity of the ligands and complexes were screened.